2016
DOI: 10.4047/jap.2016.8.6.489
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the fracture resistances of endodontically treated mandibular premolars restored with endocrowns and glass fiber post-core retained conventional crowns

Abstract: PURPOSEThis in-vitro study aimed to evaluate the fracture resistances and failure modes of endodontically treated mandibular premolars restored with endocrowns and conventional post-core retained crowns.MATERIALS AND METHODSThirty mandibular premolars were assigned into three groups (n=10): GI, intact teeth; GE, teeth with endocrowns; GC, teeth with conventional post-core supported crowns. Except for the teeth in group GI, all specimens were cut to 1.5 mm above the cementoenamel junction and endodontically tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
1
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 19 publications
7
87
1
18
Order By: Relevance
“…Furthermore, the adaptation of the inner surface of a restoration and the replication of the occlusal morphology are better [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the adaptation of the inner surface of a restoration and the replication of the occlusal morphology are better [33].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, there are clinical problems with the depth of the optical impression to record the crown, pulp chamber, and sometimes part of the canal [33].…”
Section: Discussionmentioning
confidence: 99%
“…2) 14) . In this study, 45 degrees angle was selected to mimic intraoral conditions so that the force was conducted in both the axial and the lateral directions 34) . Then, all fractured surfaces were analyzed using a stereomicroscope (Olympus SZ4045 TRPT, Osaka, Japan) at ×20 magnification to identify the failure modes.…”
Section: Fracture Test and Failure Analysismentioning
confidence: 99%
“… However, Biacchi and colleagues suggested endocrowns are best limited for molar restoration as bicuspids may present with unfavorable mastication force vectors, with Bindl et al further noting that bicuspids have less available bonding surface, greater height to width ratio, and smaller pulp chamber dimensions which all serve to intensify lever force vectors. These reports were recently reinforced by Guo and colleagues who reported that endocrowns displayed no advantage compared to conventional methods of restoring endodontically treated mandibular bicuspids. Clinically, initial reports reported approximately a 95% molar endocrown survival over 26 months, and recent results of a 7 and 10 year clinical studies are the first long‐term reports that further suggest the viability of the endocrown method …”
Section: Discussionmentioning
confidence: 99%
“…For the restoration of endodontically treated teeth, CAD/CAM advocates emphasize the “endocrown” method, which consists of a merged crown and core unit adhesively bonded into the pulp chamber and the remaining tooth structure . The endocrown method is said to provide a more conservative option to traditional post and core restorative strategies while providing equitable results . Dejak and Młotkowski using an in silico finite element analysis reported that under simulated masticatory function the endocrown had lower dentin stress concentration than compared to traditional post and core methods.…”
Section: Introductionmentioning
confidence: 99%